Peran Modal Politik dan Modal Sosial Pencalonan Suryana dan Wiwin Suwindaryati Melalui Jalur Perseorangan Pada Pilkada Kabupaten Garut Tahun 2018 - Andrian, Achmad; Wardani, Sri Budi Eko (Indonesian Democracy Research Center, 2021)
The study on the role of political and social capital in the candidacy of Suryana and Wiwin Suwindaryati through the independent route in the 2018 Garut Regency local election (Pilkada) aims to provide an overview and analysis of how these two forms of capital contributed to the candidates’ efforts to meet the minimum support requirements in the independent candidacy stage. This research adopts a qualitative approach with a descriptive method, conducted through field studies involving interviews, documentation, and literature review. The findings reveal that political capital, manifested in the candidates’ experience within religious and political organizations, as well as the support of local political elites, including religious leaders and a long-established, cohesive campaign team, played a pivotal role. When combined with social capital, reflected in the trust of Garut’s community, social relations through continuous interaction, and supportive social networks, these assets collectively strengthened Suryana and Wiwin Suwindaryati’s position in fulfilling the minimum endorsement requirements for their independent candidacy in the 2018 Garut Regency election.